Ultrafiltration behavior of monoclonal antibodies and Fc‐fusion proteins: Effects of physical properties. Issue 9 (18th May 2017) - Baek, Youngbin; Singh, Nripen; Arunkumar, Abhiram; Borys, Michael; Li, Zheng J.; Zydney, Andrew L.
ABSTRACT: Ultrafiltration (UF) is used for the final concentration and formulation of essentially all antibody‐based therapeutics including both monoclonal antibodies (mAbs) and Fc‐fusion proteins. The objective of this study was to quantitatively compare the filtrate flux behavior for two highly purified mAbs and an Fc‐fusion protein under identical flow and buffer conditions. Filtrate flux data were obtained using a Pellicon 3 tangential flow filtration cassette over a wide range of transmembrane pressures and bulk protein concentrations. Independent experimental measurements were performed to evaluate the protein osmotic pressure and solution viscosity. The maximum achievable protein concentration was directly correlated with the solution viscosity, which controls the pressure drop and extent of back‐filtration in the cassette. The filtrate flux data were analyzed using a recently developed model that accounts for the effects of intermolecular interactions and transmembrane pressure gradients on the extent of concentration polarization. These results provide important insights into the factors controlling the filtrate flux during the UF of concentrated protein solutions and an effective framework for the design/analysis of UF processes for the formulation of antibody‐based therapeutics. Biotechnol. Bioeng. 2017;114: 2057–2065. © 2017 Wiley Periodicals, Inc. Abstract : Experimental data were obtained for the ultrafiltration behavior and physical properties (viscosity, osmotic virial coefficients, and diffusivities) for two highly purified mAbs and an Fc‐fusion protein under identical flow and buffer conditions. Data were analyzed using a recently developed model that accounts for non‐ideal solution behavior and back‐filtration. The maximum achievable protein concentration was directly correlated with the viscosity of the concentrated protein solution. The results provide important insights into the factors controlling the ultrafiltration of biotherapeutics.